2018
DOI: 10.1021/acs.jafc.7b05481
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Tannins from Longan Bark as Inhibitor of Tyrosinase: Structure, Activity, and Mechanism

Abstract: In this study, the content, structure, antityrosinase activity, and mechanism of longan bark condensed tannins were evaluated. The findings obtained from mass spectrometry demonstrated that longan bark condensed tannins were mixtures of procyanidins, propelargonidins, prodelphinidins, and their acyl derivatives (galloyl and p-hydroxybenzoate). The enzyme analysis indicated that these mixtures were efficient, reversible, and mixed (competitive is dominant) inhibitor of tyrosinase. What's more, the mixtures show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 42 publications
3
66
0
Order By: Relevance
“…Several inhibition mechanisms have been reported for the tyrosinase inhibitors described above, highlighting the importance of key structural moieties as responsible for the observed effects. As an example, in silico analysis showed that the flavonoids spinosin and swertiajaponin act as competitive inhibitors of the enzyme by binding to the active site through hydrogen bonding and hydrophobic interactions [212,214], as is the case also for condensed tannins from different sources based on molecular docking [96,98,99]. Chelation of copper ions by adjacent hydroxyl groups on the B ring has also been suggested as a feasible inhibition mechanism for proanthocyanidins [101,102,106].…”
Section: Structural Requirements For the Design Of Tyrosinase Inhibitorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Several inhibition mechanisms have been reported for the tyrosinase inhibitors described above, highlighting the importance of key structural moieties as responsible for the observed effects. As an example, in silico analysis showed that the flavonoids spinosin and swertiajaponin act as competitive inhibitors of the enzyme by binding to the active site through hydrogen bonding and hydrophobic interactions [212,214], as is the case also for condensed tannins from different sources based on molecular docking [96,98,99]. Chelation of copper ions by adjacent hydroxyl groups on the B ring has also been suggested as a feasible inhibition mechanism for proanthocyanidins [101,102,106].…”
Section: Structural Requirements For the Design Of Tyrosinase Inhibitorsmentioning
confidence: 97%
“…Increasing attention has been devoted to condensed tannins, which have shown promising activities as inhibitors of both monophenolase and diphenolase activity of mushroom tyrosinase (Table 1) [96][97][98][99][100][101][102][103][104][105][106][107]. Particularly active were prodelphinidins and procyanidins from the fruit pericarp of Clausena lansium Skeels [102], as well as the complex mixtures isolated from Persea Americana [106], Longan bark [99], and from leaves and fruit of Leucaena leucocephala [97]. Very potent (IC 50 values in the range 0.10-7.5 µM) mushroom tyrosinase inhibitors have been isolated from licorice (Figure 12), the most active belonging to the isoflavan class [108][109][110] IC50 values in the range 28-42 μM have been reported for two lignans isolated from Opilia amentacea leaves [112] (Figure 13), whereas particularly effective against the monophenolase activity of the enzyme were flavonolignans from the seeds of Silybum marianum (IC50 in the range 1.7-4.9 μM) ( Figure 13) [113] as well as, although with a lower strength, hydroxylated phenones from Syzygium polyanthum leaves [114] (Figure 14).…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
See 1 more Smart Citation
“…This study group suggested that, the condensed tannins could be used to design and screen for potent novel tyrosinase inhibitors. Recently, another study (Chai et al, 2018) suggested that condensed tannins from longan bark might be a good source of tyrosinase inhibitor and could be used as novel food preservatives and medicines of skin diseases. Results showed good inhibitions on proliferation, intracellular enzyme activity and melanogenesis of mouse melanoma cells.…”
Section: ©2019 Reviews In Agricultural Sciencementioning
confidence: 99%
“…Tyrosinase expression is closely related to many physiological functions in animals. If its function is decreased or deleted, it will lead to depigmentation diseases, such as vitiligo and leukosis [4,5], while autosomal recessive diseases in animals and humans such as Parkinson's disease are also related to tyrosinase deletion or activity decreases [6][7][8]. In addition, abnormal overexpression of its activity will lead to pigmentation diseases of the human body, such as freckles, chloasma and melanoma [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%